1999
DOI: 10.1021/jp991587a
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Bond Activation by Cooperative Interaction with ns2 Atoms:  Al+ + nH2

Abstract: The reactions of Al+ + nH2 to produce AlH2 +(H2) n - 1 have been studied by high-level ab initio electronic structure techniques motivated by the σ bond activation by cooperative interaction observed experimentally and theoretically for the isovalent B+ + nH2 reaction systems. For n = 1, the reaction proceeds stepwise:  first breaking the H2 bond and forming one AlH bond followed by the formation of the second AlH bond. This process has an activation energy of 85.0 kcal/mol. For n = 2, the reaction proceeds v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Kemper et al established dissociation energies for the Al + -H 2 and Al + -͑H 2 ͒ 2 complexes of 470± 50 and 385± 50 cm −1 through measurements of the clustering equilibrium constants for the Al + -͑H 2 ͒ n−1 +H 2 Al + -͑H 2 ͒ n reactions. 9,10 One important aspect of the theoretical studies has been investigation of bond activation and formation of the inserted HAlH + species. [9][10][11] Due to the long-range charge-quadrupole interaction, the Al + -H 2 complex preferentially adopts a T-shaped structure, a bonding motif that is preserved in the larger Al + -͑H 2 ͒ n clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kemper et al established dissociation energies for the Al + -H 2 and Al + -͑H 2 ͒ 2 complexes of 470± 50 and 385± 50 cm −1 through measurements of the clustering equilibrium constants for the Al + -͑H 2 ͒ n−1 +H 2 Al + -͑H 2 ͒ n reactions. 9,10 One important aspect of the theoretical studies has been investigation of bond activation and formation of the inserted HAlH + species. [9][10][11] Due to the long-range charge-quadrupole interaction, the Al + -H 2 complex preferentially adopts a T-shaped structure, a bonding motif that is preserved in the larger Al + -͑H 2 ͒ n clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Due to the long-range charge-quadrupole interaction, the Al + -H 2 complex preferentially adopts a T-shaped structure, a bonding motif that is preserved in the larger Al + -͑H 2 ͒ n clusters. 10 Conversion of the Al + -H 2 complex to the inserted HAlH + form is predicted to proceed by breaking first the H 2 bond, followed by consecutive formation of two equivalent AlH bonds with a calculated activation energy of 85.0 kcal/ mol. Sharp et al found that the electrostatically bound Al + -H 2 complex lies 13.1 kcal/ mol lower in energy than the inserted HAlH + structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar argument was invoked to explain an analogous effect observed for the Al + /(H 2 ) 1-3 and AlH 2 + /(H 2 ) 1,2 systems. 13 Transition State Formation. One of the most interesting results of this study is the variation in transition state structure and properties with the number of H 2 molecules present.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence that 3c-2e bonding is important was inferred from the results of theoretical study of the isovalent systems, 13 Al + + nH 2 , where similar reaction mechanisms were found only for the n ) 1 and n ) 2 cases. Additional support for the important role of 3c-2e bonding was provided by a theoretical study of the isoelectronic systems, 14 Li -+ nH 2 , where a novel 3c-2e bonding scheme was identified in the transition state of the n ) 3 case.…”
Section: Introductionmentioning
confidence: 99%